Semiconducting polymer nanoparticles for multimodal biophotonics - Jiang, Yuyan (Nanyang Technological University, 2020)
Biophotonics which studies and manipulates interactions between optics and biological system plays an increasingly important role in modern biomedicine. As an emerging multidisciplinary paradigm, biophotonics converges chemistry, life sciences, optics and bioengineering, offering unique opportunities for sensitive imaging of biological or pathological events and photo-related therapeutic intervention. Despite these merits, development of biophotonics into clinical or preclinical translations is greatly hampered due to the lack of suitable photoactive biomaterials that have multimodal performance whereas minimal in vivo toxicity. With the merits of tunable photophysical properties, flexible molecular amenability and excellent biocompatibility, semiconducting polymer nanoparticles (SPNs) as a newly emerged family of optical agents make an ideal nanoplatform to perform multimodal biophotonics. However, the exploitation of SPNs in biophotonics is still in its infancy and requires substantial investigation. In this regard, research in this thesis seeks to delve into the molecular engineering of SPNs so as to explore the potential of SPNs to address the critical challenges in multimodal photonics, which include afterglow imaging with ultrahigh sensitivity, photoacoustic (PA) imaging by metabolizable contrast agents, and advanced combinational phototherapies to improve anticancer efficacy. In the first project, we design a generic approach to transforming SPNs into afterglow luminescent nanoparticles (ALNPs) for ultrasensitive in vivo imaging in deep tissue. Afterglow imaging with long-lasting luminescence after cessation of light excitation provides opportunities for ultrasensitive molecular imaging; however, the lack of versatile afterglow agents with tunable emission channels impedes its exploitation in clinical settings. In this regard, we develop a generic approach by integrating a cascade photoreaction into a single-particle entity, enabling ALNPs to chemically store photoenergy and spontaneously decay it in an energy-relay process. Not only the afterglow profiles of ALNPs can be finetuned to afford emission from visible to near-infrared (NIR) region, but also their intensities can be predicted by a mathematical model. The representative NIR ALNPs permit rapid detection of tumor in living mice with a signal-to-background that is more than three orders of magnitude higher than that of NIR fluorescence. The biodegradability of the ALNPs further heightens their potential for ultrasensitive in vivo imaging. In the second project, we synthesize metabolizable SPNs as contrast agents for PA imaging in second near-infrared (NIR-II) window. PA imaging in the second near-infrared (NIR-II) window (1000-1700 nm) holds great promise for deep-tissue diagnosis due to the reduced light scattering and minimized tissue absorption in this region; however, exploration of such non-invasive imaging technique is greatly constrained by the lack of biodegradable NIR-II absorbing agents. The metabolizable NIR-II SPNs are composed of a π-conjugated yet oxidizable optical polymer as the PA generator and a hydrolysable amphiphilic polymer as the particle matrix to provide water solubility. They are readily degraded by myeloperoxidase and lipase abundant in phagocytes, transforming themselves from the non-fluorescent nanoparticles (30 nm) into the NIR fluorescent ultra-small metabolites (~ 1 nm). As such, these NIR-II PA nanoagents can be effectively cleared out via both hepatobiliary and renal excretions after systematic administration, leaving no toxicity to living mice. More importantly, the nanoagents possess good photothermal conversion efficiencies, and emit bright PA signals at 1064 nm, enabling sensitive NIR-II PA imaging of both subcutaneous tumor and deep brain vasculature shielded by intact skull in living mice at a low systematic dosage. In addition, this study provides a generalized molecular design towards organic metabolizable semiconducting materials for biomedical optical applications in the NIR-II windows. In the third project, we make use of amphiphilic SPNs as drug delivery system to encapsulate chemotherapeutics for fluorescence/PA imaging-guided chemo-photothermal therapy. Chemo-photothermal nanotheranostics has the advantage of synergistic therapeutic effect, providing opportunities for optimized cancer therapy. However, current chemo-photothermal nanotheranostic systems generally comprise more than three components, encountering the potential issues of unstable nanostructures and unexpected conflicts in optical and biophysical properties among different components. To simplify chemo-photothermal nanotherapeutics, we synthesize an amphiphilic semiconducting polymer PEG-PCB and utilize it as a multifunctional nanocarrier. PEG-PCB has a semiconducting backbone that not only serves as the diagnostic component for NIR fluorescence and PA imaging, but also acts as the therapeutic agent for photothermal therapy. In addition, the hydrophobic backbone of PEG-PCB provides strong hydrophobic and π-π interactions with the aromatic anticancer drug such as doxorubicin for drug encapsulation and delivery. Such a trifunctionality of PEG-PCB eventually results in a greatly simplified nanotheranostic system with only two components but multimodal imaging and therapeutic capacities, permitting effective NIR fluorescence/PA imaging guided chemo-photothermal therapy of cancer in living mice. This study thus provides a molecular engineering approach to integrate essential properties into one polymer for multimodal nanotheranostics. In the fourth project, we synthesize an organic photodynamic nanoinhibitor (OPNi) to counteract carbonic anhydrase IX (CA-IX) for synergistic photodynamic therapy. Despite the great potential in cancer treatment, photodynamic therapy (PDT) often exacerbates hypoxia and subsequently compromises its therapeutic efficacy. To conquer such pitfall, OPNi is synthesized to additionally inhibit CA-IX, a molecular target in hypoxia-mediated signalling cascade. OPNi is composed of a metabolizable semiconducting polymer as the photosensitizer and a CA-IX antagonist-conjugated amphiphilic polymer as the matrix. Such a molecular structure allows OPNi not only to selectively bind CA-IX positive cancer cells to facilitate its tumor accumulation but also to regulate CA-IX-related pathway. The integration of CA-IX inhibition into targeted PDT process eventually has a synergistic effect, leading to the superior anti-tumor efficacy over sole PDT as well as the reduced probability of hypoxia-induced cancer metastasis. This study thus proposes a molecular strategy to devise simple yet amplified photosensitizers to improve traditional PDT. In the fifth project, we synthesize a hybrid semiconducting nanozyme for synergistic NIR-II photothermal ferrotherapy. Despite its growing promise in cancer treatment, ferrotherapy has low therapeutic efficacy due to compromised Fenton catalytic efficiency in tumor milieu. A hybrid semiconducting nanozyme (HSN) with high photothermal conversion efficiency is thus developed for PA imaging guided photothermal ferrotherapy in second near-infrared window. HSN comprises an amphiphilic semiconducting polymer as photothermal converter, PA emitter and iron-chelating Fenton catalyst. Upon photoirradiation, HSN generates heat not only to induce cytotoxicity but also to enhance Fenton reaction. The increased ·OH generation promotes both ferroptosis and apoptosis, oxidizes HSN (42 nm) and transforms it into tiny segments (1.7 nm) with elevated intratumoral permeability. The non-invasive seamless synergism leads to amplified therapeutic effects including a deep ablation depth (9 mm), reduced expression of metastasis-related proteins and inhibition of metastasis from primary tumor to distant organs. Thereby, this study provides a generalized nanozyme strategy to compensate both ferrotherapy and phototherapeutics for complete tumor regression. In summary, we make use of nano-engineering to transform SPNs into diversified nano-systems to perform multifunctional biophotonics. Molecular engineering of SPNs allows us to manipulate their bandgaps and regulate their internal photophysical processes to diversify their biophotonic responses. Meanwhile, nano-functionalization of SPNs provide the feasibility to modify their outer structures and inner compositions, enabling them as a multifunctional biophotonic nanoplatform. Such structural and functional versatility of SPNs in conjunction with their other intrinsic merits have helped advance the field of biophotonics, represented by their unprecedented applications ranging from ultrasensitive afterglow imaging and deep-tissue PA imaging, to versatile phototherapeutic interventions.